DZIEŁO SZTUKI A MISTERIUM PRZEMIANY - Aleksandra Pawliszyn (The Polish Journal of Aesthetics, 2011)
The aim of the text is to show the power of influence of a work of art on a human being. The power produces a specific shock in man (H.-G. Gadamer) which makes him transform his life... In this sense, it is a story touching upon aspects of Heideggerian considerations about a work of art, which have been presented in the light of so-me aspects of Merleau-Ponty’s ontology of corporeality (la chair), thus yielding recognition the truth of the truth revealed by a work in the form of apparent chasm originating from “a heart of the corporeal entity”. A specific temporality of a work of art has been shown basing on Gadamer’s philosophical hermeneutics. It organizes the existential human time into the following: the time of everyday ordinariness, the time crystallized in a work of art andthe holiday time. It turns out that a cascade of particular times released by a work of art reveals its transgressive features. A work of art, understood here as a crystallized truth, which makes us aware of the fear of death, has also been interpreted in the context of G. Bataille`s thoughts about eroticism. An author and his addressee are shown here lovers of existence, and the crystallized essence of a work of art – as an expression of human sovereignty springing up from the dew of joy and pain. All this gives evidence of a role of humancreativity in the divine grain of the Logos (Heraclitus).